2015
DOI: 10.1159/000369337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Heroin-Assisted Treatment in Belgium: A Randomised Controlled Trial

Abstract: Background/Aims: Heroin-assisted treatment (HAT) can improve the condition of heroin addicts still using street heroin after a methadone treatment. In Belgium, a new trial compared the efficacy of a HAT to existing methadone maintenance treatment. Methods: In this randomised controlled trial, HAT was limited to 12 months. Participants were assessed every 3 months. They were responders if they showed improvement on the level of street heroin use, health or criminal involvement. Results: 74 participants were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…However, a subpopulation of individuals with severe opioid use disorder are not attracted or maintained in oral maintenance treatment, and so alternative approaches are required urgently . The North American Opiate Medication Initiative (NAOMI) , along with five European randomized controlled trials, have found that injectable diacetylmorphine (DAM) (pharmaceutical heroin), delivered under supervision, to be more clinically effective than oral methadone in patients with severe opioid use disorder . Previous studies in Canada and Europe have found that DAM is cost‐saving compared to oral methadone in this patient group through its ability to reduce criminal activity .…”
Section: Introductionmentioning
confidence: 99%
“…However, a subpopulation of individuals with severe opioid use disorder are not attracted or maintained in oral maintenance treatment, and so alternative approaches are required urgently . The North American Opiate Medication Initiative (NAOMI) , along with five European randomized controlled trials, have found that injectable diacetylmorphine (DAM) (pharmaceutical heroin), delivered under supervision, to be more clinically effective than oral methadone in patients with severe opioid use disorder . Previous studies in Canada and Europe have found that DAM is cost‐saving compared to oral methadone in this patient group through its ability to reduce criminal activity .…”
Section: Introductionmentioning
confidence: 99%
“…Between January 17, 2011 and January 16, 2012, 74 participants were included in the trial: 36 participants were randomised in the experimental group and 38 in the control group. The detailed method of the trial has been already described in details [20].…”
Section: Discussionmentioning
confidence: 99%
“…Following the example of other experiments conducted in Europe [13,14,[16][17][18] and in Canada [19], a trial comparing HAT to existing MT was conducted in Belgium. The result of the study was present elsewhere [20]. We focused our present post-hoc analysis on the evolution of the criminal involvement of the 74 heroin addicts included in the trial.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable opioid agonist treatment (iOAT) is a high‐intensity therapy along the continuum of care for patients with opioid use disorder (OUD) . Prescription injectable diacetylmorphine is offered as an established standard of care for refractory OUD in several European countries . In patients who have not benefitted from oral opioid agonist treatment (OAT), injectable diacetylmorphine is effective in reducing non‐medical opioid use while improving overall health and social functioning in comparison to methadone .…”
Section: Introductionmentioning
confidence: 99%